Majas Sindiran dalam Bahasa Saluan di Desa Longkoga Barat Kecamatan Bualemo Kabupaten Banggai - Nur Aisa Hatibi; Sayama Malabar; Salam Salam (Ideas Publishing, 2023)
Emotional is characterized by words of satire. This study aims to describe the types and functions of satire majas in Saluan language. The method used is the descriptive method. The results showed (1) types of satire majas in Saluan language, namely: (a) irony Belesi hondo, (b) cynicism Bolimo mongunjang, (c) sarcasm Pateakon na komiu, (d) satire Butong um atina nodiyeqmo, and (e) innuendo sangalu sanggaat anu manohong; (2) The function of satire majas in Saluan language, which is to congregate, affirm, poetize, remind, and express certain emotional states of the heart. The Saluan language in West Longkoga Village makes satire function to express feelings to others.